2021
DOI: 10.1088/2058-6272/ac2ecf
|View full text |Cite
|
Sign up to set email alerts
|

The propagation dynamics and stability of an intense laser beam in a radial power-law plasma channel

Abstract: By containing ponderomotive self-channeling, the propagation behavior of an intense laser beam and the physical conditions are obtained theoretically in a radial power-law plasma channel. It is found that ponderomotive self-channeling results in the emergence of a solitary wave and catastrophic focusing, which apparently decreases the region for stable propagation in a parameter space of laser power and the ratio of the initial laser spot radius to the channel radius (RLC). Direct numerical simulation confirms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Various methods are possible to generate and shape a plasma channel 20,21 , making their practical application possible and thus their studies interesting. Former research demonstrated, using 2D PIC simulations, that a Gaussian beam can be well guided inside a parabolic plasma channel, and that distortions can be reduced compared to a non-parabolic plasma channel 22 , while the importance of the function that defines the plasma channel has been evidenced 23 . In this article, we propose to use a method that enables us to confidently propagate any aberrated laser beams inside a plasma channel, hence proving that even distorted beams can be converted into a single plasma mode.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are possible to generate and shape a plasma channel 20,21 , making their practical application possible and thus their studies interesting. Former research demonstrated, using 2D PIC simulations, that a Gaussian beam can be well guided inside a parabolic plasma channel, and that distortions can be reduced compared to a non-parabolic plasma channel 22 , while the importance of the function that defines the plasma channel has been evidenced 23 . In this article, we propose to use a method that enables us to confidently propagate any aberrated laser beams inside a plasma channel, hence proving that even distorted beams can be converted into a single plasma mode.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are possible to generate and shape a plasma channel 20 , 21 , making their practical application possible and thus their studies interesting. Former research demonstrated, using 2D PIC simulations, that a Gaussian beam can be well guided inside a parabolic plasma channel, and that distortions can be reduced compared to a non-parabolic plasma channel 22 , while the importance of the function that defines the plasma channel has been evidenced 23 .…”
Section: Introductionmentioning
confidence: 99%